Fear of cancer recurrence in peritoneal malignancy patients following complete cytoreductive surgery (CCRS) and hyperthermic intraperitoneal chemotherapy (HIPEC): an observational study protocol. Issue 2 (14th February 2022) - Taher, Rayan; Stanford, Sophia; Carr, Norman; Vanderpuye, Nancy; Chandrakumaran, Kandiah
Abstract : Introduction: Fear of cancer recurrence (FCR) is correlated with higher depression levels, worse quality of life and increased utilisation of healthcare services. There is no research on FCR in peritoneal malignancy (PM) patients—a rare type of abdominal cancer. This study aims to explore the prevalence, trajectory, demographic and clinical characteristics that are associated with FCR and its relationship with quality of life in PM patients. Methods and analysis: This is a cross-sectional study. Validated measures will be used to collect data on the levels of FCR (Fear of Cancer Recurrence Inventory-Short Form) and quality of life (36-Item Short-Form Health Survey) of PM patients who have had surgery in the last 5 years at the Peritoneal Malignancy Institute in Basingstoke Hospital (minimum N=260). Descriptive statistics, Pearson χ 2 tests and correlational tests will be used to analyse the data. Ethics and dissemination: Ethical approval was obtained from the HRA and Health and Care Research Wales (HCRW). The results of this study will be shared with the participants of this study, presented at conferences and PM patients' days in the form of presentations or posters, and published in a scientific journal. Discussion: The results of this exploratory study will be used to inform a multicentre observational study to explore the effect of FCR on PM patients' mental health (depression and anxiety), quality of life and healthcare utilisation which will inform a multicentre randomised controlled trial to assess the effectiveness of using evidenced-based interventions to lower FCR in PM patients.